2014
DOI: 10.1007/s11665-014-0962-3
|View full text |Cite
|
Sign up to set email alerts
|

Innovative and Highly Productive Joining Technologies for Multi-Material Lightweight Car Body Structures

Abstract: Driven by increasing costs for energy and raw material and especially by the European CO 2 -emission laws, automotive industry faces the challenge to develop more lightweight and at the same time still rigid and crash-stable car bodies, that are affordable for large-scale production. The implementation of weightreduced constructions depends not only on the availability of lightweight materials and related forming technologies, but also on cost-efficient and reliable joining technologies suitable for multi-mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
117
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 279 publications
(125 citation statements)
references
References 24 publications
0
117
0
8
Order By: Relevance
“…For materials with limited formability at ambient temperature, SPR joining may be performed with preheating of the sheet material, as described by Durandet et al (2010) using a laser, or by modifying the SPR die as shown by Drossel and Jäckel (2014). Meschut et al (2014) reported that nowadays, ultra-high strength materials and alloys are used in automotive industries, where limited deformation under load is required. Thus, it is necessary to understand the deformation behaviour of sheet material and rivet during the SPR process.…”
Section: Introductionmentioning
confidence: 99%
“…For materials with limited formability at ambient temperature, SPR joining may be performed with preheating of the sheet material, as described by Durandet et al (2010) using a laser, or by modifying the SPR die as shown by Drossel and Jäckel (2014). Meschut et al (2014) reported that nowadays, ultra-high strength materials and alloys are used in automotive industries, where limited deformation under load is required. Thus, it is necessary to understand the deformation behaviour of sheet material and rivet during the SPR process.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce CO2 emissions and minimize resource consumption, further weight reduction of a car body is demanded in the automobile industry [1,2]. Therefore, the use of high-strength steel sheets with a tensile strength of 340 MPa or higher have increased to achieve this goal.…”
Section: Introductionmentioning
confidence: 99%
“…Such structures are extensively employed in automotive [1][2][3][4], aerospace, transport and naval industries.…”
Section: Introductionmentioning
confidence: 99%